Ibogaine administration following repeated morphine administration upregulates myelination markers 2′, 3′-cyclic nucleotide 3′-phosphodiesterase (CNP) and myelin basic protein (MBP) mRNA and protein expression in the internal capsule of Sprague Dawley rats - Govender, Demi; Moloko, Leila; Papathanasopoulos, Maria; Tumba, Nancy; Owen, Gavin; Calvey, Tanya (Frontiers in Neuroscience, 2024)
Ibogaine is a psychedelic alkaloid being investigated as a possible treatment for opioid use disorder. Ibogaine has a multi-receptor profile with affinities for mu and kappa opioid as well as NMDA receptors amongst others. Due to the sparsity of research into ibogaine's effects on white matter integrity and given the growing evidence that opioid use disorder is characterized by white matter pathology, we set out to investigate ibogaine's effects on two markers of myelination, 2′, 3′-cyclic nucleotide 3′-phosphodiesterase (CNP) and myelin basic protein (MBP). Fifty Sprague Dawley rats were randomly assigned to five experimental groups of n = 10; (1) a saline control group received daily saline injections for 10 days, (2) a morphine control group received escalating morphine doses from 5 to 15 mg/kg over 10 days, (3) an ibogaine control group that received 10 days of saline followed by 50 mg/kg ibogaine hydrochloride, (4) a combination morphine and ibogaine group 1 that received the escalating morphine regime followed by 50 mg/kg ibogaine hydrochloride and (5) a second combination morphine and ibogaine group 2 which followed the same morphine and ibogaine regimen yet was terminated 72 h after administration compared to 24 h in the other groups. White matter from the internal capsule was dissected and qPCR and western blotting determined protein and gene expression of CNP and MBP. Morphine upregulated CNPase whereas ibogaine alone had no effect on CNP mRNA or protein expression. However, ibogaine administration following repeated morphine administration had an immediate effect by increasing CNP mRNA expression. This effect diminished after 72 h and resulted in a highly significant upregulation of CNPase protein at 72 h post administration. Ibogaine administration alone significantly upregulated protein expression yet downregulated MBP mRNA expression. Ibogaine administration following repeated morphine administration significantly upregulated MBP mRNA expression which increased at 72 h post administration resulting in a highly significant upregulation of MBP protein expression at 72 h post administration. These findings indicate that ibogaine is able to upregulate genes and proteins involved in the process of remyelination following opioid use and highlights an important mechanism of action of ibogaine's ability to treat substance use disorders.